The recursive formula for given sequence is:
[tex]a_n = a_{n-1} * (-4)[/tex]
Step-by-step explanation:
Recursive formula is the formula that is used to get the next term in a sequence by using the previous term
Given sequence is:
-1.5, 6, -24, 96,....
First of all we have to find the common ratio
Here
[tex]a_1 = -1.5\\a_2 = 6\\a_3 = -24\\a_4 = 96\\So,\\r = \frac{a_2}{a_1} = \frac{6}{-1.5} = -4\\r = \frac{a_3}{a_2} = \frac{-24}{6} = -4[/tex]
The recursive formula for a geometric sequence is given by:
[tex]a_n = a_{n-1}*r[/tex]
Putting the value of r
[tex]a_n = a_{n-1} * -4[/tex]
Hence,
The recursive formula for given sequence is:
[tex]a_n = a_{n-1} * (-4)[/tex]
Keywords: Geometric sequence, common ratio
Learn more about geometric sequence at:
#LearnwithBrainly